Paleomagnetism of Siluro-Devonian rocks from eastern Maine - Kent, Dennis V.; Opdyke, Neil D. (Canadian Journal of Earth Sciences, 1980)
A diverse suite of rocks was collected for paleomagnetic study from two formations in the Eastport area of northeastern Maine: 18 sites (103 samples) from redbeds and diabase sills of the Hersey Formation (uppermost Silurian to Lower Devonian) and 14 sites (74 samples) from lavas, redbeds, and calcareous nodules of the Eastport Formation (Lower Devonian; Rb/Sr age 412 Ma). Characteristic magnetizations based on AF and thermal demagnetization analyses give mean directions, after simple correction for bedding tilt, of D = 163.6°, I = 41.3°, α 95 = 6.3°, for N = 16 sites in the Hersey, and D = 179.3°, I = 38.0°, α 95 = 9.4°, for N = 14 sites in the Eastport Formation. Baked contact relations, the presence of opposite polarities, and the similarity in directions over different rock types and magnetic carriers point to an acquisition of magnetization near to the time of rock formation. The mean directions correspond to (south) paleopole positions at 19.8°S lat., 308.8°E long. (δp, δm = 4.7°, 7.7°) for the Hersey and 23.7°S lat., 293.7°E long. (δp, δm = 6.6°, 11.1°) for the Eastport Formation.These paleopoles are removed from the Upper Silurian Bloomsburg Formation pole, but are in reasonable agreement with similar age results from central Newfoundland, suggesting that the Acadia displaced terrain encompassed these areas. Siluro-Devonian paleopoles from intrusive rocks in northeastern North America are generally widely divergent and these may not be providing an accurate record of paleomagnetic field in all cases.